Progress of Clinical Research on Prevention and Treatment of Type 2 Diabetes Mellitus with Nonalcoholic Fatty Liver by Traditional Chinese Medicine - Li, Yi; Lu, Bo; Ding, Yu (Journal of Contemporary Medical Practice, 2024)
Both type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver (NAFLD) are metabolic diseases, which often affect each other and occur simultaneously. Insulin resistance is the common pathogenesis of both. According to the pathogenesis and clinical manifestations of T2DM with NAFLD, modern doctors classify it as "diabetes disease" combined with "accumulation" or "hypochondriac pain". It is believed that the disease is mainly related to congenital deficiency, improper diet, poor mood and excessive work and rest. Disease location involves liver, spleen, kidney three viscera, disease is mostly the deficiency of the deficiency of liver, spleen and kidney, qi stagnation, blood stasis, phlegm-dampness obstruction as the standard. Give full play to the unique advantages of the whole concept of TCM and the thought of syndrome differentiation and treatment, so as to reduce symptoms, reduce recurrence and regulate the metabolism of the body. In recent years, new progress has been made in the study of T2DM complicated with NAFLD by traditional Chinese medicine. Now, the etiology and pathogenesis of T2DM complicated with NAFLD are systematically reviewed, which provides new ideas for the clinical diagnosis and treatment of T2DM complicated with NAFLD.